Achirality via graphs - Azram, Mohammad (Pushpa Publishing House, 2010)

(untitled)
This article is devoted to establish relationship between knots and planar graphs. This relationship enables us to investigate the total number of regions and their relationship with corresponding crossings in a reduced alternating achiral knot. It has been shown that the number of regions in a reduced alternating achiral knot is always even and the number of crossing is always two less than the number of regions. Finally, we establish necessary conditions for achirality.